The financial implications of cardiac stress testing prior to abdominal aortic aneurysm repair. (October 2022) - Ponukumati, Aravind S; Columbo, Jesse A; Suckow, Bjoern D; Stableford, Jennifer A; Henkin, Stanislav; Beach, Jocelyn M; Goodney, Philip P; Stone, David H
Background: The utilization and cost-effectiveness of stress testing before abdominal aortic aneurysm (AAA) repair remains insufficiently studied. We examined the variation and financial implications of stress testing, and their association with major adverse cardiovascular events (MACE). Methods: We studied patients who underwent elective endovascular (EVAR) or open AAA repair (OAR) at Vascular Quality Initiative centers from 2015 to 2019. We grouped centers into quintiles of preoperative stress testing frequency. We calculated the risk of postoperative MACE, a composite of in-hospital myocardial infarction, heart failure, or death, for each center-quintile. We obtained charges for stress tests locally and applied these to the cohort to estimate charges per 1000 patients. Results: We studied 32, 459 patients (EVAR: 27, 978; OAR: 4481; 283 centers). Stress test utilization varied across quintiles from 13.0% to 68.6% (median: 36.8%) before EVAR and 15.9% to 85.0% (median: 59.4%) before OAR. The risk of MACE was 1.4% after EVAR and 10.2% after OAR. There was a trend towards more common MACE after EVAR among centers with higher utilization of stress testing: 0.9% among centers in the lowest quintile, versus 1.7% in the highest quintile ( p -trend = 0.068). There was no association between MACE and stress testing frequency for OAR ( p -trend = 0.223). The estimated financial charges for stress testing before EVAR ranged from 125, 806 per 1000 patients at 1 st -quintile centers, to 665, 975 at 5 th -quintile centers. Charges before OAR ranged from 153, 861 at 1 st -quintile centers, to 825, 473 at 5 th -quintile centers. Conclusion: Stress test use before AAA repair is highly variable and associated with substantial cost, with an unclear association with postoperative MACE. This highlights the need for improved stress testing paradigms prior to surgery.